Augmented Reality-Based Car Showroom Application as a Promotional Media at Alya Motor Car Showroom - Kandiaz, Muhammad; Ekawati , Nia (Internet of Things and Artificial Intelligence Journal, 2024)
In today's fast-paced world, transportation is crucial in facilitating the movement of people and goods. As a popular means of land transportation, automobiles have continuously evolved with advanced technologies to enhance fuel efficiency and driving safety. Established in 2014, Alya Motor has served hundreds of customers using social media platforms for marketing. However, innovative marketing strategies are essential to enhance the shopping experience, especially amidst declining purchasing power. This research aims to design, implement, and test a car showroom application based on Augmented Reality (AR) as a promotional medium for Alya Motor. An Android application was developed using Blender, Unity 3D, and Vuforia to offer an interactive car viewing experience. The research followed the Multimedia Development Life Cycle (MDLC) methodology, ensuring a user-centric approach. The application was successfully tested, achieving an 86% acceptance rate in User Acceptance Testing (UAT). The AR-based application significantly improves the promotional strategy by providing potential buyers with an engaging and effective shopping experience.